ESTIMATION OF CARBON STOCK IN MANGROVE ECOSYSTEM BASED ON SUSTAINABLE CARBON TRADING FULFILLMENT IN THE COASTAL OF JAVA ISLAND FOR 2016-2021 - Bertrand Altawirano Wibisono, Michael
This study aims to determine and estimate the area of mangrove cover, density distribution and estimation of carbon stock in biomass on the coast of Java Island based on carbon trading needs. Estimation was carried out in 2016-2021 using remote sensing methods and field measurements. The data used in this research consist of the following: (i) Landsat 8 satellite imagery, (ii) drone imagery and (iii) in-situ data to detect the vegetation lattice and the area production of specific mangrove vegetation areas on Rhizopora and Avicennia. Calculation of carbon stock follows the above ground vegetation biomass or known as the Above-Ground Carbon (AGC). Mangrove cover detection with satellite involving multispectral imagery and vegetation index (Vegetation Index) is found to be faster, cheaper, and better for the purpose of regional study. Support Vector Machine (SVM) method that accompanied by learning datasets are used for classifying mangrove vegetation areas and nonmangrove areas. The Enhanced Vegetation Index (EVI) is also used to strengthen the classification on the density and health level of mangrove vegetation. The Allometric equation is used to calculate the AGC and CO2 absorption potential. It was found that the mangrove area on the coast of Java decreased from 7048.11 ha in 2016 to 2947.68 ha in 2021. In addition, the measured carbon stock dropped from the value of 545.35 tC/ha (2016) to 226.92 tC/ha (2021) and the carbon absorption potential reduced from 1999.63 tCO2/ha to 832.04 tCO2/ha.